Characterization of the complete mitochondrial genome of Eopsetta grigorjewi (Herzenstein, 1890) (Chordata: Pleuronectidae) from the Yellow Sea and its phylogenetic implications. Issue 9 (2nd September 2022) - Guo, Dong; Zhang, Dandan; Tu, Zhong; Yan, Long; Wang, Weikuang
Abstract: In this study, we determined the complete mitochondrial genome (mitogenome) of Eopsetta grigorjewi Herzenstein, 1890 (Chordata: Pleuronectidae) using Sanger sequencing technology. The total length of the mitogenome sequence of E. grigorjewi is 17, 269 base pairs, including 13 protein-coding genes (PCGs), 22 transfer RNA genes, and two ribosomal RNA genes. The overall composition of the mitogenome is estimated to be 27.5% A, 25.6% T, 29.9% C, and 17.0% G. The phylogenetic relationships of 15 Pleuronectidae species were constructed based on the 13 PCGs by the maximum-likelihood approach using IQtree software.